2012
DOI: 10.1002/j.2205-0140.2012.tb00013.x
|View full text |Cite
|
Sign up to set email alerts
|

The development, structure and blood flow within the umbilical cord with particular reference to the venous system

Abstract: The umbilical cord is a helical and tubular blood conduit connecting the foetus to the placenta. The umbilical cord achieves its final form by the 12th week of gestation and normally contains two arteries and a single vein, all embedded in Wharton's jelly. The structure of the umbilical cord receives only a cursory glance during many obstetric ultrasound examinations: with imaging limited to documenting the number of vessels within the cord and the insertion sites at the foetus and placenta. Extensive research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(91 citation statements)
references
References 19 publications
(35 reference statements)
0
84
0
7
Order By: Relevance
“…The histological images of dHUC revealed a spongy tissue. Additionally, the dHUC tissue stained positively for both collagen type I (Figure A) and hyaluronic acid (Figure B), the two most abundant matrix components in umbilical cord tissue . The images demonstrated an even distribution of these extracellular matrix components throughout the tissue (Figure D).…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…The histological images of dHUC revealed a spongy tissue. Additionally, the dHUC tissue stained positively for both collagen type I (Figure A) and hyaluronic acid (Figure B), the two most abundant matrix components in umbilical cord tissue . The images demonstrated an even distribution of these extracellular matrix components throughout the tissue (Figure D).…”
Section: Resultsmentioning
confidence: 94%
“…Histological assessment revealed that the primary native ECM components found in the Wharton's jelly of umbilical cord tissue, collagen I and HA, are retained in dHUC after processing (Figure ). Because dHUC allografts are devitalized, cell nuclei are intact and still present in the tissue, as shown by DAPI staining.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Human umbilical cord is a structure connecting fetus to the placenta and it develops at 4 th to 8 th weeks of pregnancy, while the blood circulation within the cord is established by the end of the 5 th week. At term, it is 40-60 cm long and 1-2 cm wide [10]. Several main regions of the cord can be distinguished, speifically an outer single layer of amniotic epithelium, the subamnion, the intervascular Wharton's jelly and a perivascular region, that surrounds the umbilical vessels (two arteries and one vein) [9].…”
Section: Histological Characterization Of Human Umbilical Cordmentioning
confidence: 99%